Effect of Limb Power, Arm Power, Hand Eye Coordination on the Combination of Punches and Kicks of Martial Arts Athletes - Jeki Purnama Putra; Nurlan Kusmaedi; Mulyana Mulyana; Amung Ma’mun (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Low achievement in the sport of martial arts is influenced by several factors in the direction of physical condition and the ability to combine punches and kicks. This type of research is quantitative research with an associative correlation approach with a method (path analysis). The purpose of this study is to determine the influence both directly and indirectly of the combination of punches and kicks. The sample in this study was 30 athletes, the sampling technique used purposive sampling technique. Punch and kick combination test to measure athlete's attack combination ability, Vertical Jump measures limb power, two hand medicine ball put measures arm power and hand-eye coordination with tennis ball catch throw In this limb power instrument has a validity value of 0.67, and test reliability of 0.79. Data analysis techniques use path analysis techniques. Results show 1). The direct effect of limb power on the combination of punches and kicks of Riau Holy Site athletes is 6.30%. 2). Direct influence of arm power on the combination of punches and kicks of Riau Holy Site athletes 8.47%, 3). The direct influence of eye-hand coordination on the combination of punches and kicks of Riau Holy Site athletes 23.04. This research only discusses a few factors that affect the combination of punches and kicks of athletes, there are many other factors such as agility, speed, accuracy, etc. That way, it is hoped that there will be further research that examines other variable factors so that all aspects that can affect the combination of punches and kicks can be analyzed and get answers so that they can improve the achievements of Indonesian martial arts athletes, especially Riau sacred site athletes. Keywords: Limb Power, Arm Power, Hand Eye Coordination, Combination of Punch, Kick